Hydrogen-bonded organic frameworks (HOFs): a new class of porous crystalline proton-conducting materials - Karmakar, Avishek; Illathvalappil, Rajith; Anothumakkool, Bihag; Sen, Arunabha; Samanta, Partha; Desai, Aamod V.; Kurungot, Sreekumar; Ghosh, Sujit K. (Angewandte Chemie-International Edition, 2016)
Two porous hydrogen-bonded organic frameworks (HOFs) based on arene sulfonates and guanidinium ions are reported. As a result of the presence of ionic backbones appended with protonic source, the compounds exhibit ultra-high proton conduction values (sigma) 0.75x 10(-2)Scm(-1) and 1.8x10(-2)Scm(-1) under humidified conditions. Also, they have very low activation energy values and the highest proton conductivity at ambient conditions (low humidity and at moderate temperature) among porous crystalline materials, such as metal-organic frameworks (MOFs) and covalent organic frameworks (COFs). These values are not only comparable to the conventionally used proton exchange membranes, such as Nafion used in fuel cell technologies, but is also the highest value reported in organic-based porous architectures. Notably, this report inaugurates the usage of crystalline hydrogen-bonded porous organic frameworks as solid-state proton conducting materials.
Keywords: guanidinium; hydrogen-bonded organic frameworks; porous crystalline frameworks; proton conduction; sulfonates

Ultrahigh ionic conduction in water-stable close-packed metal-carbonate frameworks - Manna, Biplab; Desai, Aamod V.; Illathvalappil, Rajith; Gupta, Kriti; Sen, Arunabha; Kurungot, Sreekumar; Ghosh, Sujit K. (Inorganic Chemistry, 2017)
Utilization of the robust metal-carbonate backbone in a series of water-stable, anionic frameworks has been harnessed for the function of highly efficient solid-state ion conduction. The compact organization of hydrophilic guest ions facilitates water-assisted ion-conduction in all the compounds. The dense packing of the compounds imparts high ion-conducting ability and minimizes the possibility of fuel crossover, making this approach promising for design and development of compounds as potential components of energy devices. This work presents the first report of evaluating ion-conduction in a purely metal-carbonate framework, which exhibits high ion-conductivity on the order of 10(-2) S cm(-1) along with very low activation energy, which is comparable to highly conducting well-known crystalline coordination polymers or commercialized organic polymers like Nafion.

Ultralight crystalline hybrid composite material for highly efficient sequestration of radioiodine - Fajal, Sahel; Mandal, Writakshi; Torris, Arun; Majumder, Dipanjan; Let, Sumanta; Sen, Arunabha; Kanheerampockil, Fayis; Shirolkar, Mandar M.; Ghosh, Sujit K. (Nature Communications, 2024)
Considering the importance of sustainable nuclear energy, effective management of radioactive nuclear waste, such as sequestration of radioiodine has inflicted a significant research attention in recent years. Despite the fact that materials have been reported for the adsorption of iodine, development of effective adsorbent with significantly improved segregation properties for widespread practical applications still remain exceedingly difficult due to lack of proper design strategies. Herein, utilizing unique hybridization synthetic strategy, a composite crystalline aerogel material has been fabricated by covalent stepping of an amino-functionalized stable cationic discrete metal-organic polyhedra with dual-pore containing imine-functionalized covalent organic framework. The ultralight hybrid composite exhibits large surface area with hierarchical macro-micro porosity and multifunctional binding sites, which collectively interact with iodine. The developed nano-adsorbent demonstrate ultrahigh vapor and aqueous-phase iodine adsorption capacities of 9.98 g.g-1 and 4.74 g.g-1, respectively, in static conditions with fast adsorption kinetics, high retention efficiency, reusability and recovery. The development of effective adsorbents of radioiodine nuclear waste remains difficult due to the lack of proper material design strategies. Here the authors report an ultralight hierarchically porous crystalline multifunctional hybrid nanocomposite for ultrafast entrapment of iodine and polyiodide species under both static and dynamic condition.